Attrition of Patients on a Precision Oncology Trial: Analysis of the I‐PREDICT Experience. (2nd October 2020) - Bohan, Sandy S.; Sicklick, Jason K.; Kato, Shumei; Okamura, Ryosuke; Miller, Vincent A.; Leyland‐Jones, Brian; Lippman, Scott M.; Kurzrock, Razelle
Abstract: Background: Precision oncology uses molecular profiling of tumors to identify biomarker‐tailored therapies for patients in the hope of improving outcomes. Typically, only a minority of patients receives evaluable matched treatment. This study explored the reasons for attrition on a precision medicine trial. Materials and Methods: Study participants were 190 adult patients who consented to the I‐PREDICT (Investigation of molecular Profile‐Related Evidence Determining Individualized Cancer Therapy) trial. Patients had metastatic and/or unresectable incurable malignancies. Patients who were not evaluable were analyzed. Results: Of consented patients, 44% were not evaluable. Men were twice as likely to be not evaluable as women. Prominently, 45% of patients who were not evaluable dropped off because of death, hospice referral, or decline in organ function. Conclusion: Health deterioration of consented patients is a significant barrier to being evaluable on the I‐PREDICT trial. These data suggest that patients are enrolled on precision oncology trials too late in their disease course or with excessive disease burden. Abstract : Few studies have focused on patient attrition in the context of personalized oncology studies. This article examines factors contributing to the loss of patients enrolled in a precision medicine trials.